Reading problems among primary school remedial pupils in one of Miri, Sarawak / Ivy Jain and Norasmah Othman - Jain, Ivy; Othman, Norasmah (Penerbit UiTM (UiTM Press), 2019)
Reading is a difficult skill to be mastered by children mainly remedial students prone to problems in basic reading skill. Remedial students are students with learning disabilities who have been selected to attend the Remedial Programme in their schools. This study was conducted to identify the problems faced by these students in mastering basic reading skill. Basic reading skill that is the focus of this article is the open syllables words; Consonant Vowel Consonant Vowel (KVKV). This study aimed to identify the main problems faced by students in reading open syllables words (KVKV). The study was conducted in one elementary school in the district of Miri, Sarawak involving 30 pupils in year two from remedial class. Data were collected through Diagnostic Tests, observations and interviews in the study group. The study found that the main problems were; students do not understand the basic concepts of reading clearly and the lack of motivation among the students. This study is expected to help teacher in particular remedial teachers in helping students overcome reading recovery KVKV word. To improve the reading skills of pupils, the study recommended that remedial students are taught by a variety of teaching strategies such as inserting games or songs in their teaching and learning in order to cultivate their interest in reading. Teachers are also advised to constantly motivate the students so that they are eager to learn the skills of reading.